Wakaf Linked Sukuk Dalam Perspektif Maqashid Syari’ah - Mohammad Farid Fad (UIN Walisongo Semarang, 2021)
Based on BWI’s data, the potential for wakaf money in Indonesia reaches at least IDR 180 trillion (www.gomuslim.co.id, 2017) per year. But in reality, the assets of large waqf funds are not necessarily linear with the level of welfare of the Muslim community in Indonesia. In addition, it is necessary to revitalize the endowment of money to revive its vital role. One way is to collaborate between Sukuk and money waqf agreements. The Waqf Linked Sukuk (WLS) can be seen as an ongoing financing instrument that Islam is trying to help maintain the ratio of public spending from, for and by the people. Furthermore, WLS can be an important innovation for economic sustainability, especially to finance micro-communities without interest rates. Whereas the WLS contract needs to be reviewed in favor of the public benefit from the perspective of maqashid shari'ah. This research uses a qualitative approach. Data collection methods used in this study are literature, documentation and interview methods. In analyzing the data that has been collected, researchers will use descriptive-analytical analysis with the ushuliyah approach. The results of this study are waqf and sukuk which consist of 2 different product orientations, namely Tabarru and Tijaroh, which are transformed and correlated in an effort to realize greater benefit value. The legal basis for allowing this WLS product is Q.S. Al-Maidah verse 1, Q.S. al-Isra 'verse 34, Q.S. Al-Baqarah verse 275, the hadith of the Prophet, fiqh rules are